2010
DOI: 10.1111/j.1600-0609.2010.01424.x
|View full text |Cite
|
Sign up to set email alerts
|

Whole brain radiation alone produces favourable outcomes for AIDS‐related primary central nervous system lymphoma in the HAART era

Abstract: Primary central nervous system lymphoma (PCNSL) related to acquired immunodeficiency syndrome (AIDS) is a lethal disorder, but the recent application of highly active antiretroviral therapy (HAART) has significantly improved prognosis. This retrospective cohort study of AIDS-related PCNSL examined the actual clinical outcomes and prognostic variables affecting overall survival (OS) in the HAART era. Twenty-three newly diagnosed AIDS-related PCNSL at 12 regional centre hospitals for HIV/AIDS in Japan between 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 27 publications
0
19
0
1
Order By: Relevance
“…Use of either WBRT or chemotherapy independently reduced the risk of death in a large retrospective HIV-PCNSL cohort [91]. HD-MTX-based regimens have been tolerated in immunodeficient patients, but trials in the cART era are lacking [97] and data is particularly scarce on patients receiving combination chemotherapy [92, 98]. There is an isolated case report of successful ASCT [99].…”
Section: Treatmentmentioning
confidence: 99%
“…Use of either WBRT or chemotherapy independently reduced the risk of death in a large retrospective HIV-PCNSL cohort [91]. HD-MTX-based regimens have been tolerated in immunodeficient patients, but trials in the cART era are lacking [97] and data is particularly scarce on patients receiving combination chemotherapy [92, 98]. There is an isolated case report of successful ASCT [99].…”
Section: Treatmentmentioning
confidence: 99%
“…Several studies have evaluated either calendar period [15,27] or HAART use [1618,23,40] as prognostic factors. Building on our previous work, this is the first study to independently evaluate calendar period and individual HAART data in strictly defined AR-PCNSL cases.…”
Section: Discussionmentioning
confidence: 99%
“…[55,57,58] A German study of non-HIV-related PCNSL showed no advantage of radiotherapy combined with methotrexate over methotrexate alone, [58] while a Japanese study of HIV-associated PCNSL reported prolonged survival with radiotherapy combined with HAART. [57] Meanwhile, ganciclovir has been shown to prolong survival and eradicate CSF EBV. [59] Chemotherapy and radiotherapy are both associated with major side effects, including leucopenia, liver toxicity, and leukoencephalopathy.…”
Section: Central Nervous System Lymphoma and Other Tumorsmentioning
confidence: 99%
“…[59] Chemotherapy and radiotherapy are both associated with major side effects, including leucopenia, liver toxicity, and leukoencephalopathy. [57,58] Irrespective of treatment regimen, better performance status at diagnosis improves survival. [57,58] Taking all these into consideration, patients with HIV-associated PCNSL should probably all receive a combination of HAART, ganciclovir, and methotrexate.…”
Section: Central Nervous System Lymphoma and Other Tumorsmentioning
confidence: 99%
See 1 more Smart Citation